Emojis and Law: contextualized flexibility of meaning in cyber communication. Issue 3 (26th May 2020) - Wagner, Anne; Marusek, Sarah; Yu, Wei
ABSTRACT: Because some sentiments simply cannot be verbalized, the written message lacks rendered intonation and the embodied dynamics of expressed feeling. With the rise of emails and other means of digital communication, the emotive shortcomings of new communication channels are even more acute even while they become emotively more expansive. The color, form, and context of emojis in visual communication may lead to more kinds of (mis)interpretation. Although emojis might be presented as a tool for clarification of the communicative intent, it is still unknown whether visual add-ons also introduce more uncertainty or flexibility in language. As a result, emojis contribute to a digital cultural shift in message transmission that also reflects an evolving hermeneutic of legal communication and communicative intention. In a growing number of legal cases, emojis serve as evidence, or as facts which reveal asserted, yet unsaid information and implied meaning. This study depicts the flexible nature of emojis in e-communication, and so analyzes applications in various legal cases to demonstrate the way emojis, as negative emotional influencers, affect the understanding of online communication and decision-making in courts.